Compression of dementia morbidity by higher education - Then, F. S.; Luck, Tobias; Matschinger, H.; Angermeyer, M. C.; Riedel-Heller, Steffi Gerlinde (Elsevier BV, 2016)
Objectives: The concept of compression of morbidity suggests that compressing cognitive morbidity into a shorter lifetime period would result in a better cumulative lifetime cognitive functioning. Some lifestyle factors, like higher education, that are known to protect cognitive functioning in old age and lower dementia risk, could compress cognitive morbidity. Therefore the aim of our study was to investigate whether higher education leads to a better cumulative lifetime cognitive functioning and, hence, the compression of cognitive morbidity. Methods: Data were derived from the population-based Leipzig longitudinal study of the aged (LEILA75+). From 1998-2005, individuals aged 75 years and older underwent up to seven assessments at a 1.5-year interval and a long-term follow-up assessment after 15 years (2013). Analyses on the impact of higher education on compression of cognitive morbidity were carried out via multilevel logistic mixed-models and tobit analyses using the participants’ age as time scale (n=742). Results: The results revealed that more years of education were significantly associated with a better cognitive functioning but not with the age at dementia onset or the age at death. Computation of cumulative lifetime cognitive functioning was weighted for survival probability and indicated a gain of 21 MMSE points during the lifetime period 75 through 100 years of age by having more than 12 years of education compared to having less than 9 years of education. Conclusion: Overall, the findings suggest a compression of cognitive morbidity by higher education prior to dementia onset. More years of education could therefore contribute to a better cognitive functioning even under consideration of survival probability. Hence, efforts to ensure access to higher education for as many people in a population as possible might compress disease burden due to cognitive morbidity.